Self-reported oral health-related quality of life and caries experiences of 5-year-old children in Mandalay, Myanmar - Saw Nay Min; Duangporn Duangthip; Sherry Shiqian Gao; Palinee Detsomboonrat (BMC, 2024)
Abstract Background This study aimed to examine the impact of dental caries and other potential socio-demographic factors on the oral health-related quality of life (OHRQoL) of preschool children from Myanmar. This was done using the Scale of Oral Health Outcomes for 5-year-old children (SOHO-5) as reported by both the children and their parents. Methods A structured questionnaire was conducted to collect demographic information about the children and their caregivers, as well as socioeconomic data. The OHRQoL was assessed by interviewing the children and their parents using the Myanmar versions of SOHO-5c and SOHO-5p, respectively. Caries experience was assessed by two calibrated examiners and recorded using the dmft index. The Poisson regression model was adopted to investigate the association between OHRQoL and dental caries including socioeconomic factors. Results A total of 454 pairs participated in the study. Among them, 64% of children and 70% of parents reported a negative impact on OHRQoL (with SOHO-5c and SOHO-5p scores exceeding 0). The mean score (SD) of the child self-report and parental version of the SOHO-5 was 1.86 (2.27) and 2.65 (3.13), respectively. Difficulties in eating and sleeping were the most commonly reported by both children and parents. The overall prevalence of dental caries was 87% (mean dmft score:5.59, SD:4.65). The final multivariate-adjusted model revealed that children with higher caries experiences were more likely to have lower OHRQoL for both child self-report (RR 4.38, 95% CI 3.16-6.14, p < 0.001) and parental report (RR 6.07, 95% CI 4.38-8.41, p < 0.001), respectively. A lower family income had a negative impact on the children's OHRQoL in child self-report (RR 1.59, 95% CI 1.26-2.04, p < 0.001) and parental report (RR 1.46, 95% CI 1.19-1.78, p < 0.001). Conclusion Two-thirds of the study children and their parents perceived the negative impact on children's OHRQoL. Higher caries experience and lower family income were associated with poorer OHRQoL of 5-year-old Myanmar children.